Perkembangan Munasabah al-Qur’an Era Klasik-Modern - Said Ali Setiyawan (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2019)
The existence of the mun?sabah al-Qur'?n is disputed among the scholars, between the pros and cons. The majority of scholars agree that there is a mun?sabah in the Qur'an. However, the study of this theme has not been done so much, even though it is very important especially in the realm of the interpretation of the Koran to get a good and holistic understanding, not partiality. The author expresses it with a descriptive-analytical method so that this study can be understood more clearly and practiced better. This research produced several important points: 1] mun?sabah al-Qur'?n is a useful science to find out the systematic reasons for the placement of parts of the Qur'an, 2] periodization of the development of mun?sabah al-Qur'?n: classical, middle and modern; 3] The main form of mun?sabah al-Qur'?n is inter-verse and inter-surah, 4] The method of mun?sabah al-Qur'?n is observing the purpose of the suras; observe the preamble of the surah; observing the stages of the mun?sabah-early part of the letter; and pay attention to various possibilities that arise from the reader's mind.